(3GdLRGFQ aj GdJGQjN (B/s - (3SYOj, YKeGfs ((3GdLRGFQ (B:s (3OGQ GdCeI ddfTQ h GdJhRjY ,s, 2013)
(3GdcJGH jJchf ef NeSI aUhd GdaUd GdGhd Yf bHd GdJGQjN h GdYgO Gdajfjbj h GdYgO GdQheGfj h GdKGfj Yf GdaJM GdGSdGej MJi GdbQf JGdSGOS GdYTQ GdejdGOj h geG jZWjGf JGQjN GdeZQH GdYQHj cdg GdaUd GdKGdK Yf GdYgO GdYKeGfj HGdLRGFQ h GdaUd GdQGHY Yf GdGMJdGd GdaQfSj h GdebGheI GdLRGFQjI h GdaUd GdNGeS Yf GdMQcI GdhWfjI GdLRGFQjI eY GdJQcjR Ydi eYgO YHO GdMejO Hf HGOjS HbSfWjfI GdPj aJM SfI (B1947(3e cGYXe eDSSI JYdjejI aj JGQjN GdLRGFQ h jJhba GdcJGH aj SfI (B1954s
Keywords: (3GdLRGFQs; (3JGQjNs